Tests of Alternative Theories of Firm Growth - Evans, David S. (Journal of Political Economy, 1987)
This study examines the relationships among firm growth, firm size, and firm age for a sample of manufacturing firms between 1976 and 1982. Firm growth is found to decrease with firm age and firm size. These findings are robust to alternative assumptions concerning the effects of sample censoring and the functional form of the growth relationship. The inverse growth-age relationship is consistent with a theory of firm learning proposed by Boyan Jovanovic while the inverse growth-size relationship is inconsistent with a number of theories that assume or imply Gibrat's law. Copyright 1987 by University of Chicago Press.